Cryptosporidium oocyst wall proteins are true components of the oocyst wall and COWP8 is not required for parasite transmission - Bacchetti, Ross; Stevens, Sarah; Lemgruber, Leandro; Gonzalez Oliva, Mariana Azevedo; Sands, Emma M.; Alexandrou, Konstantinos; Tinti, Michele; Robinson, Lee; Hanna, Jack C.; Seizova, Simona; Goddard, Peyton; Vassalli, Massimo; et al. (PLOS Pathogens, 2025)
Cryptosporidiosis is a significant cause of diarrhoeal disease contributing to substantial morbidity and mortality for the immunocompromised and for young children, especially those who are malnourished. There are no vaccines and no effective treatments for these patients. Cryptosporidium parasites are transmitted as an oocyst, which is composed of a hardy oocyst wall that protects parasites in the environment. Oocysts are often waterborne, and are resistant to common water treatments, including chlorination. Little is understood about how the Cryptosporidium oocyst is constructed, its composition, and the how it resists chlorination. A family of nine Cryptosporidium Oocyst Wall Proteins (COWPs) is predicted from the genome. However, due to the technical challenges of working with this parasite in the laboratory, only cowp1 has been investigated to date. Using CRISPR/Cas9, fluorescent fusions were generated for the remaining members of the family, COWPs 2–9. Microscopy confirms that all COWPs localise to the oocyst wall. Further, COWPs 2–4 appear to localise specifically to the oocyst suture, the site from which parasites emerge from the oocyst during infection. Cowp 6 and 8 were observed to be expressed by female parasites. These proteins localise to puncta consistent with organelles called wall forming bodies. These organelles store and then secrete material to form the oocyst wall. Parasites lacking cowp8 produce viable oocysts that have typical oocyst morphology. Cowp8 knockout oocysts are transmissible under laboratory settings and readily infect immunocompromised mice. Biomechanical measurements determine that COWP8 is not required for the strength of the oocyst wall. This work confirms the role of cowps in oocyst wall formation and sets a foundation for further exploration of the role of these proteins in transmission of Cryptosporidium parasites.